Bv8 mediates myeloid cell migration and enhances malignancy of colorectal cancer - Li, Xiaomeng; Chang, Enqiang; Cui, Jiang; Zhao, Hailin; Hu, Cong; O’Dea, Kieran P.; Tirlapur, Nikhil; Balboni, Gianfranco; Zhang, Jiaqiang; Ying, Liming; Ma, Daqing (Frontiers in Immunology, 2023)
Colorectal cancer (CRC) is the third most predominant malignancy in the world. Although the importance of immune system in cancer development has been well established, the underlying mechanisms remain to be investigated further. Here we studied a novel protein prokineticin 2 (Prok2, also known as Bv8) as a key pro-tumoural factor in CRC progression in in vitro and ex vivo settings. Human colorectal tumour tissues, myeloid cell lines (U937 cells and HL60 cells) and colorectal cancer cell line (Caco-2 cells) were used for various studies. Myeloid cell infiltration (especially neutrophils) and Bv8 accumulation were detected in human colorectal tumour tissue with immunostaining. The chemotactic effects of Bv8 on myeloid cells were presented in the transwell assay. Cultured CRC cells treated with myeloid cells or Bv8 produced reactive oxygen species (ROS) and vascular endothelial growth factor (VEGF). Furthermore, ROS and VEGF acted as pro-angiogenesis buffer in myeloid cell-infiltrated CRC microenvironment. Moreover, myeloid cells or Bv8 enhanced energy consumption of glycolysis ATP and mitochondria ATP of CRC cells. Interestingly, myeloid cells increased CRC cell viability, but CRC cells decreased the viability of myeloid cells. ERK signalling pathway in CRC cells was activated in the presence of Bv8 or co-cultured myeloid cells. In conclusion, our data indicated the vital roles of Bv8 in myeloid cell infiltration and CRC development, suggesting that Bv8 may be a potential therapeutic target for colorectal cancer-related immunotherapy.